PERAN SUPERVISI PENGAWAS, MEMODERASI PENGARUH PENDIDIKAN DAN PELATIHAN DAN MOTIVASI TERHADAP KINERJA GURU (Studi Pada Sekolah Dasar Di Kecamatan Bandar Kabupaten Batang) - Purwoto, Purwoto (Students Journal of Economic and Management, 2012)
The study was conducted to determine the role of inspectors supervised, Moderate the influence of education and training and motivation on the performance of elementary school teachers in the district Bandar of Batang district. WithÂ 139 people in the sample respondents of the member of teachers 229 people in there. The method of determining the number of samples with a probability sampling technique proportionate stratified random sampling. Our primary data taken between the month of July â August 2012. Once processed with SPSS-16 program validity and reliability of test results declared infalid questionnariaes LF > 0,4 and reliable with a cronbach alpha > 0,7. Skewness and Kurtosis Normality normal with number below critical limit of 1,96. F test and t test with the result of each significance value below 0,05 so the model said to fit and independent variables significant influence. Once the data is processed by a computer SPSS-16 program, it was concluded that; 1) Education and training are significantly positive effect on teacher performance, 2) Motivation negative significant effect on the teacher performance, 3)Supervision Supervisor significant negative effect on the performantce of teacher, 4)Supervision moderating significantly negative effect on the performance of the teacher training and 5) Supevision significantly positive moderating effect of motivation on teacher performance. Keyword: Trainning, Motivation, Supervision, Performance, Moderate and Influence